Collision-energy dependence of deuteron cumulants and proton-deuteron correlations in Au+Au collisions at RHIC - M.I. Abdulhamid; B.E. Aboona; J. Adam; L. Adamczyk; J.R. Adams; I. Aggarwal; M.M. Aggarwal; Z. Ahammed; E.C. Aschenauer; S. Aslam; J. Atchison; V. Bairathi; et al. (Physics Letters B, 2024)
We report the first measurements of cumulants, up to 4th order, of deuteron number distributions and proton-deuteron correlations in Au+Au collisions recorded by the STAR experiment in phase-I of Beam Energy Scan (BES) program at the Relativistic Heavy Ion Collider. Deuteron cumulants, their ratios, and proton-deuteron mixed cumulants are presented for different collision centralities covering a range of center-of-mass energy per nucleon pair sNN=7.7 to 200 GeV. It is found that the cumulant ratios at lower collision energies favor a canonical ensemble over a grand canonical ensemble in thermal models. An anti-correlation between proton and deuteron multiplicity is observed across all collision energies and centralities, consistent with the expectation from global baryon number conservation. The UrQMD model coupled with a phase-space coalescence mechanism qualitatively reproduces the collision-energy dependence of cumulant ratios and proton-deuteron correlations.